Effect of dietary crude protein level on reproductive traits of commercial pigeons in different production terms - Meleg, István; Dublecz, Károly; Vincze, L.; Horn, Péter (Acta Agraria Kaposváriensis, 1999)
The experiment was conducted to measure the effects of feeding diets containing 12, 14, 16, 18 and 20% crude protein to utility pigeons in the first and second production terms. The traits studied were: egg production, egg weight, hatchability of eggs laid, mortality of breeding pairs, growth of squabs up to weaning and feed intake. 30 breeding pairs per treatment were kept in pears in a specially designated three tier cage system, in a windowless environmentally controlled house at a constant 12-hour light period throughout the year. The test period was 12 months in each production terms. Different protein levels failed to affect the length of egg cycle, annual egg production, egg weight, hatchability of eggs laid and mortality of squabs. Increasing dietaiy crude protein content and the weaning weight of squabs increased significantly (P < 0.001). Annual squab production and feed intake of parents increased when higher protein diets were fed. The feed conversion ratio of squabs decreased with increase in the protein content of diet.
Keywords: pigeon; diet; protein; reproduction; meat